2010
DOI: 10.1007/s10560-010-0213-x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Social Competence in Adolescents and Mothers’ Parenting Style: A Cross Sectional Study on Iranian Girls

Abstract: This study is to determine the association between parenting style of mothers and the social competence of their adolescent daughters in effective communication, problem solving skills and use of basic social skills dimensions. The data were gathered for the mean age of 11-15 years on 737 Iranian adolescent girls in a cross sectional study design. The parenting style of mothers was based on their demand and responsiveness. These scales classified mothers into four parenting styles as follows: authoritative, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
4
19
0
14
Order By: Relevance
“…On the other hand, adolescents from indulgent families, characterized by acceptance/involvement but not strictness/imposition, showed high self-reliance and self-competence, but also showed higher levels of substance abuse and school problems Radziszewska, Richardson, Dent, & Flay, 1996). These patterns did not vary neither as a function of adolescents' age or sex (Aunola et al 2000;Barton & Kirtley, 2012;López-Jáuregui & Oliden, 2009), nor as a function of parents' sex (Kazemi, Ardabili, & Solokian, 2010;Martínez, García, Camino, & Camino, 2011;Martínez, García, Musitu, & Yubero, 2012).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…On the other hand, adolescents from indulgent families, characterized by acceptance/involvement but not strictness/imposition, showed high self-reliance and self-competence, but also showed higher levels of substance abuse and school problems Radziszewska, Richardson, Dent, & Flay, 1996). These patterns did not vary neither as a function of adolescents' age or sex (Aunola et al 2000;Barton & Kirtley, 2012;López-Jáuregui & Oliden, 2009), nor as a function of parents' sex (Kazemi, Ardabili, & Solokian, 2010;Martínez, García, Camino, & Camino, 2011;Martínez, García, Musitu, & Yubero, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…In Spain, García and Gracia (2010) found that adolescents from indulgent homes obtained better scores in different indicators of psychological adjustment, such as emotional stability and positive worldview, than those from authoritative families; Garaigordobil and Aliri (2012) found that the indulgent style of parenting promote the fewest sexist attitudes in youth; Torre, Casanova, García, Carpio, and Cerezo (2011) found that the indulgent style showed a lowest level of stress; and, López-Romero, Romero and Villar (2012) found that the indulgent style was less related to psychopathic personality in childhood. Other studies in Spain (Alonso-Geta, 2012; Gamez-Guadix, Jaureguizar, Almendros, & Carrobles, 2012;García & Gracia, 2009;, Italy (DiMaggio & Zappulla, 2013;Marchetti, 1997), Turkey (Turkel & Tezer, 2008), Germany (Wolfradt, Hempel, & Miles, 2003), Mexico (Villalobos, Cruz, & Sánchez, 2004), Brazil (Martínez & García, 2008;Martínez, García, & Yubero, 2007), Iran (Kazemi et al, 2010) and Philippines , reported similar findings.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…De esta forma, se ha comprobado que no hay diferencias en el rendimiento académico de los adolescentes filipinos (Hindin, 2005) y de los coreo-americanos (Kim y Rohner, 2003) educados con estilos autorizativo e indulgente. El mismo patrón de resultados se ha encontrado para las competencias sociales de las adolescentes iraníes (Kazemi, Ardabili y Solokian, 2010). Del mismo modo, en países de Sudamérica, como México (Villalobos, Cruz y Sánchez, 2004) y Brasil (Martínez y García, 2008), se ha encontrado que los hijos de padres indulgentes obtienen los mismos o mejores resultados que los hijos de padres autorizativos en distintas medidas de ajuste social y psicológico.…”
unclassified
“…Estos trabajos, junto con los realizados en otras culturas diferentes a la anglosajona (Dor y Cohen-Fridel, 2010;Kazemi et al, 2010;Martínez y García, 2008;Turkel y Tezer, 2008), están cuestionando la generalización transcultural de los resultados de la investigación desarrollada en este área durante los últimos 50 años. El efecto de prevención o riesgo que los diferentes estilos de socialización parental puedan tener sobre el consumo de sustancias tiene particular interés, ya que en la actualidad se debate que algunas variables tradicionalmente consideradas de prevención para el consumo, como la alta autoestima, puedan estar actuando como tales (Fuentes, García, Gracia y Lila, 2011).…”
unclassified